Synergistic effect of Mg and Y co-dopants on enhancement of electrochemical properties of LiNi0.5Mn1.5O4 spinel. (10th December 2021) - Lin, Fangchang; Guo, Jianbing; Wang, Liyuan; Zhou, Ying; Wu, Hongming; Zhou, Dengfeng
Highlights: A new magnesium and yttrium co-doping strategy was designed to synthesize LNMO. The synergism of Mg and Y co-doping was investigated. MgY cathode material exhibits optimal cycling stability and rate performance. Abstract: The LiNi0.5– x Mgx Mn1.48 Y0.02 O4 ( x  = 0.005, 0.01, 0.03) and LiNi0.5 Mn1.5 O4 (LNMO) cathode materials were synthesized successfully through a citric acid aided route. The relationship between material characteristics (structure and morphology) and electrochemical properties of LNMO cathode materials was investigated. It was found that synergistic effect of co-doped magnesium and yttrium ions resulted in marked enhancement of electrochemical properties of LNMO cathode. SEM observation showed that Mg-Y co-doped samples possessed spinel structure with truncated octahedron morphology. After co-doping Mg and Y, the XRD and TEM analyses showed that lattice parameters for LNMO samples were improved, thus improving the rate and cycling property. XPS results of Mg-Y co-doped spinel LiNi0.5 Mn1.5 O4 indicated the presence of Mg 2+ and Y 3+ in the spinel lattice. Notably, LiNi0.49 Mg0.01 Mn1.48 Y0.02 O4 exhibited both optimal cycling stability and rate performance. LiNi0.49 Mg0.01 Mn1.48 Y0.02 O4 sample retained specific capacity of 131 mAh g −1 after 100 cycles at high current density of 1 C with superior retention of 98.49% and the specific capacity reached 118 mAh g −1 at 5 C. While undoped sample only retained 107 mAh g −1 after 100 cycles at 1 C with lower retention of 94.69% and its specific capacity was 84 mAh g −1 at 5 C. Graphical abstract: New magnesium and yttrium co-doping strategy was designed and LiNi0.5-x Mgx Mn1.48 Y0.02 O4 ( x  = 0.005, 0.01, 0.03) sample was obtained via citric acid aided route to enhance the electrochemical property of LiNi0.5 Mn1.5 O4 cathode material for the first time. Image, graphical abstract